Tuberculosis treatment within differentiated service delivery models in global HIV/TB programming. (28th October 2021) - Tran, Cuc H.; Moore, Brittany K.; Pathmanathan, Ishani; Lungu, Patrick; Shah, N. Sarita; Oboho, Ikwo; Al‐Samarrai, Teeb; Maloney, Susan A.; Date, Anand; Boyd, Andrew T.
Abstract: Introduction: Providing more convenient and patient‐centred options for service delivery is a priority within global HIV programmes. These efforts improve patient satisfaction and retention and free up time for providers to focus on new HIV diagnoses or severe illness. Recently, the coronavirus disease 2019 (COVID‐19) pandemic precipitated expanded eligibility criteria for these differentiated service delivery (DSD) models to decongest clinics and protect patients and healthcare workers. This has resulted in dramatic scale‐up of DSD for antiretroviral therapy, cotrimoxazole and tuberculosis (TB) preventive treatment. While TB treatment among people living with HIV (PLHIV) has traditionally involved frequent, facility‐based management, TB treatment can also be adapted within DSD models. Such adaptations could include electronic tools to ensure appropriate clinical management, treatment support, adherence counselling and adverse event (AE) monitoring. In this commentary, we outline considerations for DSD of TB treatment among PLHIV, building on best practices from global DSD model implementation for HIV service delivery. Discussion: In operationalizing TB treatment in DSD models, we consider the following: what activity is being done, when or how often it takes place, where it takes place, by whom and for whom . We discuss considerations for various programme elements including TB screening and diagnosis; medication dispensing; patient education, counselling and support; clinical management and monitoring; and reporting and recording. General approaches include multi‐month dispensing for TB medications during intensive and continuation phases of treatment and standardized virtual adherence and AE monitoring. Lastly, we provide operational examples of TB treatment delivery through DSD models, including a conceptual model and an early implementation experience from Zambia. Conclusions: COVID‐19 has catalysed the rapid expansion of differentiated patient‐centred service delivery for PLHIV. Expanding DSD models to include TB treatment can capitalize on existing platforms, while providing high‐quality, routine treatment, follow‐up and patient education and empowerment.